Thyroid-Like Low-Grade Nasopharyngeal Papillary Adenocarcinoma with Biphasic Histology - Rusella Mirza; Nestor Dela Cruz; Guillermo A. Herrera (Case Reports in Pathology)
Thyroid-like low-grade nasopharyngeal papillary adenocarcinoma (TL-LGNPPA) is a rare primary adenocarcinoma of nasopharynx. The immunohistochemical pattern of this tumor is similar to that of papillary thyroid carcinoma making this neoplasm a challenging diagnosis. A case of TL-LGNPPA with biphasic morphology is presented. The removed tumor from the nasopharynx exhibited a polypoid appearance. Microscopically, it was composed of papillary structures admixed with a few solid areas of spindle cells. The papillae were lined by columnar epithelium. Both the epithelium and the spindle cells were strongly positive for TTF-1 and CK19 and negative for CK5/6, S-100, and thyroglobulin. Cellular atypia, necrosis, and high mitotic rate were absent. Ki67 was less than 2% in the neoplastic cells. No local recurrence or distant metastasis was reported after 12 months of follow-up. Caution should be taken to differentiate TL-LGPPA from other TTF-1-positive neoplasms, especially papillary thyroid carcinoma, as the prognosis for these two tumors is entirely different.